Ghrelin Levels in Male Patients with Hyperlipoproteinemia I, II versus Type 2 Diabetes Mellitus. - Abbas, Salma A.; Shkhaier, Samir L.; Abed, Baydaa A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background; Hyperlipoproteinemia (HLP) are divided in primary and secondary subtypes. Primary HLP is usually due to genetic causes. Secondary HLP is resulting from another underlying disorder such as diabetes mellitus that leads to alterations in plasma lipid and lipoprotein metabolism, HLP may be idiopathic . Patients and Methods; Ninety male individuals (age 30-45)years were enrolled in this study which were divided into three groups as follows:- (G1) consist of 30 healthy male individuals as a control group, (G2) consist of 30 male patients with (HLP) without any other disease (15 of them were HLP1,the other were HLP11), (G3) consist of 30 male patients with DM2 without any other disease .(Ghr), fasting blood glucose (FBG), c-peptide, Insulin, Insulinresistance (IR), Insulin sensitivity (S%), Beta cell function(B%) ,Glucose/ Insulin ratio, triacylglycerol(TG),total cholesterol (TC), low density lipoprotein(LDL),high density lipoprotein(HDL),very low density lipoprotein(VLDL),TC/HDL ratio, LDL/HDL ratio and atherogenic index of plasma(AIP) were evaluated .Objectives; The aims of this paper were to evaluate the differences in the ghrelin hormone (Ghr) levels between healthy control and patients with primary hyperlipoproteinemia [hyperlipoproteinemia I (HPLI) , hyperlipoproteinemia II (HPLII)] and secondary hyperlipoproteinemia [ type 2 diabetes mellitus(DM2)], and study the relation of (Ghr) with other parameters. Results; The mean level of Ghr was significantly lower (P<0.05) in DM2 compared with control group, significantly higher(P<0.05) in HLP1 compared with HLP11 and DM2 and significantly higher(P<0.05) in HLPII compared with DM2. There were significant correlations between Ghr level and (insulin, c-peptide ,IR,S% ,TG ,VLDL ,AIP) in patients with DM2 and significant correlations between Ghr level and (TG ,LDL ,VLDL ,LDL/HDL ratio ,c-peptide ,S%)in patients with HLPI. Conclusion; We conclude that low plasma Ghr level is closely related to atherogenicity in DM 2 patients while there is no significant relationship between them in HLPI and HLPII.